Teacher leadership: that strengthens professional practice - Danielson, Charlotte (Association for Supervision and Curriculum Development, 2020)
Provides a foundation for developing and supporting highly committed teacher leaders. Including advice for administrators and practical tips for experienced and aspiring teacher leaders, this book presents a clear plan for ensuring that teacher leadership is a powerful force for school improvement.